Series Wound DC Motor Simulation Applying MATLAB SIMULINK and LabVIEW Control Design and Simulation Module - Szíki, Gusztáv Áron; Sarvajcz, Kornél; Szántó, Attila; Mankovits, Tamás (Periodica Polytechnica Transportation Engineering, 2020)
In our previous publication a model for series wound direct current (SWDC) motors was described and a simulation program was presented which is based on the above model and was developed in MATLAB environment. In the publication mentioned above, the measurement process of the parameters (bearing resistance torque, electric resistances, dynamic inductances) of the SWDC motor was also described. From the parameters the program calculates the current intensity, rpm and torque of the motor as a function of time. The recent publication is about the realization of the above program applying the Control Design and Simulation Module of NI LabVIEW. This module enables the adjustment of input parameters (e.g. supply voltage) during the running of the program, thus the realization of real time driving simulation. In addition, among others, it can be applied with data acquisition, GPIB, CAN, and FPGA (field-programmable gate array) hardware platforms of National Instruments.